Analisis Kinerja Petugas Polisi Pamong Praja Dalam Pelaksanaan Tugas Monitoring Dan Evaluasi di Kabupaten Nias Utara - Martianus Zalukhu; Sukaaro Waruwu; Peringatan Harefa; Shopia Molinda Kakisina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
This research aims to analyze the performance of Municipal Police Officers in the execution of monitoring and evaluation tasks in North Nias Regency. The research method used is analytical descriptive with a qualitative approach. Data were collected through interviews, observations, and documentary studies on the activities of Municipal Police Officers. The research results show that the performance of Municipal Police Officers in monitoring and evaluation tasks in North Nias Regency has several aspects that need attention. Overall, there is success in the implementation of these tasks, but there are also some challenges such as a lack of training and understanding of monitoring and evaluation tasks. In addition, the availability of resources and supporting facilities also affects the performance of officers. Recommendations are provided to improve the performance of Municipal Police Officers through increased training, understanding of duties, and improved access to resources and supporting facilities. It is hoped that the results of this research can serve as consideration for relevant parties in enhancing the effectiveness and efficiency of monitoring and evaluation tasks of Municipal Police Officers in North Nias Regency.